A Study on High Strength Concrete by Partial Replacement of Sand with Laterite Sand In Concrete - V. S. Chitra, Keerthan Kondapalli, Srinivas Kunchala, Anusha Guguloth, Pulsu Rakesh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Concrete is the most widely used composite material today. The constituents of concrete are coarse aggregate, fine aggregate, binding material, and water. A rapid increase in construction activities leads to an acute shortage of conventional construction materials. Conventionally, sand is being used as fine aggregate in concrete. The function of the fine aggregate is to assist in producing workability ad uniformity in the mixture. The river deposits are the most common source of fine aggregate. So there are great demands within the construction industries for river sand as fine aggregate used in the production of concrete. This has created a very difficult situation, also there is great fear from environmentalist and the ecology will be distorted. Hence, the need to find the materials which are affordable and available partially or totally replaced river sand in the production of concrete. Hence, we are forced to think the alternative materials. This report aims to present the study done to establish scientific data regarding the compressive strength and tensile strength of concrete on partial replacement of fine aggregate with laterite soil in concrete mix of High-Performance Concrete M100 grade. The sand shall be replaced gradually in the mentioned grade of concrete by 0%, 10%, 20%, 30%, 40% and 50% with laterite soil and the specimen shall be tested at curing intervals of 3days, 7days, and 28days. For compressive strength and at curing interval of 3days, 7days, and 28days for tensile strength for 28 days